2013
DOI: 10.1021/nn405236k
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Controlled Synthesis of PbS and PbSe Quantum Dots with in Situ Halide Passivation for Quantum Dot Solar Cells

Abstract: We developed a simple non-hot-injection synthetic route that achieves in situ halide-passivated PbS and PbSe quantum dots (QDs) and simplifies the fabrication of Pb-chalcogenide QD solar cells. The synthesis mechanism follows a temperature-dependent diffusion growth model leading to strategies that can achieve narrow size distributions for a range of sizes. We show that PbS QDs can be produced with a diameter as small as 2.2 nm, corresponding to a 1.7 eV band gap, while the resulting size distribution (6-7%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
338
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(362 citation statements)
references
References 39 publications
19
338
1
4
Order By: Relevance
“…These approaches can be classified by synthesis strategy (e.g., hot injection, 11,12 heat-up, 13 or continuous flow 14 ) and precursor chemistry (e.g., PbO and bis(trimethylsilyl)sulfide (TMS-S), 11,14,15 PbO and substituted thioureas, 16 lead acetate (PbAc) and TMS-S, 17,18 PbCl 2 and elemental sulfur, 19,20 PbCl 2…”
Section: Introductionmentioning
confidence: 99%
“…These approaches can be classified by synthesis strategy (e.g., hot injection, 11,12 heat-up, 13 or continuous flow 14 ) and precursor chemistry (e.g., PbO and bis(trimethylsilyl)sulfide (TMS-S), 11,14,15 PbO and substituted thioureas, 16 lead acetate (PbAc) and TMS-S, 17,18 PbCl 2 and elemental sulfur, 19,20 PbCl 2…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless surprisingly high mobilities were reported lately by several groups, [12][13][14][15][16][17][18] in high quality films made of different materials, suggesting that band-like transport through extended states is indeed achievable in CQD arrays, provided the surface traps are effectively passivated [18][19][20][21][22][23][24][25] and the separation between dots is reduced sufficiently by the use of extremely short ligands or inorganic capping. 26 This hypothesis is supported by the observed temperature dependence of mobility and conductivity [12][13][14][15][16][17][18] whereas the spectral broadening and red shifts of the 1S exciton peak observed in these systems, 13,27 may be indicative of strong electronic coupling between QDs, as are the remarkable values of diffusion lengths and lifetimes of charge carriers measured in QD solids.…”
mentioning
confidence: 99%
“…However, (TMS) 2 S and (TMS) 2 Se are flammable and toxic, and they readily hydrolyze with water to form toxic H 2 S and H 2 Se. This has led to the development of methods based on alternative precursors, including lead(II) chloride instead of PbO as the lead precursor to improve the surface passivation of the resulting CQDs [68,72], and elemental sulfur instead of (TMS) 2 S [73,74]. Additional novel growth methods have been proposed, including the synthesis of PbSe in a phosphate glass host [75].…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…Studies have shown that device air stability and efficiency are greatly increased when the CQD active material is treated with Cl-containing ligands [16,72]. Several specific methods have been developed that take advantage of the properties of halogen ligands.…”
Section: Ligand Typesmentioning
confidence: 99%